(untitled) (Fiep Bulletin - online, 2024)
Access to learning chess in Physical Education classes presents itself as a challenge for teaching. Because of this, chess practices must be approached from the perspective of an instrument of social interaction, committed to the formation of critical citizens and active in the teaching-learning process in different areas. Supported by the conception of chess as a highly complex interactive activity in the production of meanings. This work consists of investigating chess practices in physical education classes. From a methodological point of view, this is a qualitative research, carried out in a municipal elementary school, located in the city of Timon-MA. To generate data, we used projects, lesson plans and registration forms. As a result, we noticed that the majority of students sought to learn the game, although the material conditions were not favorable and that the discouragement of some were realities, overcome by the majority who set out to develop the practice of chess. Furthermore, chess practices 6th and 7th year classes are limited.